Marketization and Varieties of Accountability Relationships in Employment Services: Comparing Denmark, Germany, and Great Britain. Issue 3 (March 2018) - Jantz, Bastian; Klenk, Tanja; Larsen, Flemming; Wiggan, Jay
In the past decade, European countries have contracted out public employment service functions to "activate" working-age benefit clients. There has been limited discussion of how contracting out shapes the accountability of employment services or is shaped by alternative democratic, administrative, or network forms of accountability. This article examines employment service accountability in Germany, Denmark, and Great Britain. We find that market accountability instruments are additional instruments, not replacements. The findings highlight the importance of administrative and political instruments in legitimizing marketized service provision and shed light on the processes that lead to the development of a hybrid accountability model.